COVID–19 Pandemic Lockdown: A Comparative Analysis of Government Intervention between Palliatives in Nigeria and Stimulus in United States of America (USA) - Odedokun, Ezekiel Adeyemi (NIU Journal of Social Sciences, 2021)
Coronavirus or COVID – 19 pandemic has caused a crisis of monumental dimension for the global economy with an escalating number of confirmed cases on a daily basis. The declaration of the virus by the World Health Organization (WHO) as a global pandemic is an indication that it will have a sustained global impact. Thus, in response to this, governments of many nations have embarked on several and different initiatives to counteract the disruption caused by coronavirus as well as providing for those affected by the pandemic. This paper did a comparative analysis between what the governments of the United States of America (USA) and that of Nigeria rolled out to neutralize the negative effects of the pandemic. While Nigeria represents the developing nations, the USA represents the advanced nations of the world. The paper draws on a desk–based review of secondary data and literature. Also, individual comments were analyzed to understand the contents of the series of relief initiatives by governments. The paper concludes that while the advance nations, represented by the USA, provide their citizens with economic stimulus, the developing nations, represented by Nigeria provide palliatives. The difference between the two is that; palliatives are meant to lessen the pains inflicted by the pandemic while stimulus causes growth and activity. Therefore, the paper recommends that what Nigerians need is stimulus as against the various palliatives which cannot eradicate but lessen hardship. Keywords: Coronavirus, Pandemic, Palliatives, Stimulus, Economy.